Familial occurrence of imperforate hymen in premature monozygotic twins and their mother: a case report and literature review - Chua, Bernadine Han Ern; Amin, Zubair; Ng, Yvonne Peng Mei (Frontiers in Pediatrics, 2024)
Background: Imperforate hymen is an uncommon obstructive anomaly of the developing female reproductive tract. There are occasional case reports of imperforate hymen in family clusters suggesting plausible familial mode of inheritance. We describe a set of monozygotic premature twins with imperforate hymen noted at birth, whose mother was diagnosed with the same condition as a teenager. We also elucidate the likely underlying mode of inheritance of imperforate hymen. Method: We utilized CARE (Case Report) Guideline in reporting the cases. Case presentation: This is a set of monozygotic twins born prematurely at 30 weeks’ gestation who were noted to have a bulging cyst-like structure protruding from their vagina at birth, which were diagnosed as imperforate hymens. The twins were not dysmorphic nor had any other congenital malformations. Over the next few weeks, these cyst-like structures (mucoceles) became less prominent. The genital anomaly was diagnosed as an imperforate hymen. Their mother was also diagnosed with an imperforate hymen when she was 12 years old and was treated with a hymenectomy. Discussion: This unique occurrence of imperforate hymen in a set of premature monozygotic twins and their mother suggests plausible autosomal or X-linked dominant mode of inheritance. As genetic inheritance can play a role in the development of an imperforate hymen, it is important to look out for this genital anomaly in female relatives of an index case.